Strategic Analysis Of 101 Corporations\'s Ability To Sustain Its Competitiveness In The Oil Palm Industry - Mason, Cordelia (2009)
This thesis is the entire case study of IOI Corporation Berhad which incorporates the findings in Part 1 - industry analysis of the oil palm industry, and Part 2 - analysis of IOI\'s corporate structure and growth patterns, to conduct a strategic analysis of IOI Corporation\'s ability to sustain its competitiveness in the oil palm industry.